2014
DOI: 10.1177/2158244014551716
|View full text |Cite
|
Sign up to set email alerts
|

Case Study of a School-Based Universal Dating Violence Prevention Program

Abstract: Evaluation of universal dating violence prevention programs has rapidly expanded in the past two decades. Many programs demonstrate change in attitudes supportive of dating violence, and a few show evidence of behavior change; however, detailed analysis of process and fidelity of program implementation is generally neglected. An important goal of prevention research is to identify successful initiatives that can be replicated and disseminated in the field. The purpose of the current case study is to document t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The majority (n = 104, 65.0%) of interventions were evaluated in single-arm studies, while 24 interventions (15.0%) 78,80,94,100,105,123,[177][178][179] were compared with at least one other active intervention.…”
Section: Process and Implementation Evaluations (Rq2)mentioning
confidence: 99%
See 2 more Smart Citations
“…The majority (n = 104, 65.0%) of interventions were evaluated in single-arm studies, while 24 interventions (15.0%) 78,80,94,100,105,123,[177][178][179] were compared with at least one other active intervention.…”
Section: Process and Implementation Evaluations (Rq2)mentioning
confidence: 99%
“…In 10 studies, ethnicity was mixed and no one race or ethnic group accounted for more than 50% of students. 91,101,114,126,202,207,[213][214][215][216] The remaining studies reported a majority black or African American 80,137,178,217 or Hispanic or Latino…”
Section: Ethnicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Dating Matters is a primary prevention effort focused on 6 th to 8 th graders in urban, high crime neighborhoods (Tharp, 2012). Prevention programs are most frequently implemented in school-based settings, as either part of a health class curriculum or in afterschool settings (Cascardi & Avery-Leaf, 2014; Hickman, Jaycox, & Aronoff, 2004; Malhotra, Gonzalez-Guarda, & Mitchell, 2015). Evaluation studies have shown some promising results of these interventions; for example, a recent meta-analysis of 23 school-based interventions (10 in middle schools, 13 in high schools) showed significant changes in knowledge and attitudes across studies, though not in perpetration or victimization (De La Rue, Polanin, Espelage, & Pigott, 2017).…”
Section: Introductionmentioning
confidence: 99%